INNOVATION OF TECHNOLOGY ON IMMIGRATION SERVICES, SPECIFICALLY ON MANUFACTURING A PASSPORT IN THE IMMIGRATION OFFICE WITH THE APPLICATION OF EPS SYSTEM (EXPRESS PASSPORT SERVICE) - Wilonotomo Wilonotomo; Bagas Hidayat Putra (Polteknik Imigrasi, 2018)
Along with the development of technology to the era of globalization as it is currently demanding every performance or human activity to be more effective and faster in its completion. Including in immigration services to Indonesian Citizens related to making passports for applicants who are increasing in number every day and are required to be faster in the settlement process in order to improve the level of performance and results of applicant satisfaction that will be achieved in immigration services. Where to achieve this goal, it is supported by a technological innovation in immigration services in making passports that produce faster and better quality output by applying an EPS (Express Passport Service) system.